2008
DOI: 10.1007/bf03346437
|View full text |Cite
|
Sign up to set email alerts
|

Absence of thyrotropin-induced increase in leptin levels in patients with history of differentiated thyroid carcinoma undergoing recombinant human thyrotropin testing

Abstract: Our in vivo experimental model suggests that an acute TSH increase after rhTSH testing is ineffective in changing circulating leptin levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…We can speculate a direct effect of TSH on lipids, and not mediated by cytokine. Indeed, a previous report found that adipocytokine could interact with thyroid hormone [30,31], but acute effect of rhTSH is ineffective in changing leptin levels [32].…”
Section: Discussionmentioning
confidence: 99%
“…We can speculate a direct effect of TSH on lipids, and not mediated by cytokine. Indeed, a previous report found that adipocytokine could interact with thyroid hormone [30,31], but acute effect of rhTSH is ineffective in changing leptin levels [32].…”
Section: Discussionmentioning
confidence: 99%
“…Whether rhTSH effect on serum leptin persists beyond the length of this study cannot be established at this time, since blood sampling was stopped at 96 h after the first rhTSH administration, according to the standard protocol for thyroglobulin measurement in thyroid cancer patients. In a recent study, no significant variations in serum leptin concentrations after in vivo stimulation with rhTSH were reported (26). The small number of subjects and different times of observation of TSH effects might explain the lack of significant changes in serum leptin observed in that study.…”
Section: Discussionmentioning
confidence: 54%